Training and Education for Orphanage Children to Realize Sustainable Economic Independence In Al-Marhamah Orphanage - Adnans, Abdhy Aulia; Hadiyani, Sherry; Ivana Putri; Muhammad Suriya Pratama; Nurjannah Angelina; Surbakti, Ahmad Maulana; Cindy Aprilia Naumi (Talenta Publisher, 2022)
Not all children have the opportunity to get the fulfillment of the right to develop properly. Therefore, a forum is formed that is ready to facilitate these less fortunate children, one of which is the Orphanage. Al-Marhamah Orphanage is one of the orphanages located in Medan Sunggal. Al-Marhamah orphanage does not have a permanent donor and only lives from the proceeds of the business which is sold in front of the orphanage building. The types of products sold also have low competitiveness, so there needs to be an increase in capabilities in the culinary and business fields as well as optimal empowerment of human resources. Based on this, community service is carried out in the form of achievement motivation training, culinary training, and digital marketing education. In addition, recipe books and other supports are provided as needed. Educational training and debriefing carried out using lecture, demonstration, practice, as well as direct discussion and question and answer. The results of the implementation show that the target can participate in all series of activities with a positive attitude, and have the provisions to be able to realize sustainable economic independence.